PUBLIC FINANCIAL MANAGEMENT SYSTEM (PFMS) IN INDIA: INTRODUCTION AND EVALUATION IN THE CONTEXT OF INDIAN EDUCATION SYSTEM - Aniruddhabhi, Raval Dipal; Shah, Khusbu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Public Financial Management System (PFMS) is a comprehensive digital platform developed by the Government of India to ensure effective management of public funds. Introduced under the Ministry of Finance, PFMS aims to enhance transparency, accountability, and efficiency in financial transactions related to centrally sponsored schemes and welfare programs. This article explores the structure and mechanism of PFMS and evaluates its implementation in the context of the Indian education system. With a specific focus on educational schemes such as Samagra Shiksha Abhiyan, Mid-Day Meal Program, and various student scholarship initiatives, the study highlights how PFMS has facilitated real-time fund tracking, direct benefit transfers, and improved financial governance. The article also assesses the successes, challenges, and limitations of PFMS, and offers policy recommendations for enhancing its functionality and outreach. The findings suggest that while PFMS has significantly improved fund flow management and reduced inefficiencies in education finance, there remains a need for infrastructural improvements, capacity building, and better integration to maximize its impact.